Synergistic piezophotocatalytic and photoelectrochemical performance of poly(vinylidene fluoride)–ZnSnO3 and poly(methyl methacrylate)–ZnSnO3 nanocomposites. Issue 49 (14th June 2017) - Lin, Hung-Ming; Chang, Kao-Shuo
Abstract : This study investigated the piezophotocatalytic and photoelectrochemical (PEC) properties of poly(vinylidene fluoride) (PVDF)– and poly(methyl methacrylate) (PMMA)–ZnSnO3 (ZTO) nanocomposites. Abstract : This study investigated the piezophotocatalytic and photoelectrochemical (PEC) properties of poly(vinylidene fluoride) (PVDF)– and poly(methyl methacrylate) (PMMA)–ZnSnO3 (ZTO) nanocomposites. The multifunctions exhibited by a single compound, ZTO, were considered, and the properties were further enhanced through intimate coupling with PVDF or PMMA by using hydrothermal and spin-coating techniques to achieve synergistic piezo-related performance. PVDF and PMMA were used to enhance the separation of fabricated ZTO nanowires and improve the effective contact between nanocomposites and stress sources in various measurements including piezopotential, piezotronic, piezophototronic, and piezophotocatalytic analyses. PVDF– and PMMA–ZTO samples exhibited average piezopotentials of approximately 10 and 6 mV, respectively. Their piezotronic and piezophototronic effects were ascertained by examining current–voltage characteristics. In addition, the Schottky behavior and Schottky barrier height variation (Δ Φ p 2−0.1 ) for the two systems were deduced quantitatively by using the thermionic emission–diffusion theory ( e.g., Δ Φ p 2−0.1 decreased by approximately 50 mV for the PVDF–ZTO nanocomposite at S2 under 0.6 GPa and −4.9 V). Energy band diagram evolution and intimate coupling between ZTO and polymers were proposed to contribute to the superior piezo-related output. The piezophotocatalytic reaction rate constant (approximately 11.4 × 10 −3 min −1 ) of PVDF–ZTO was higher than that of the ZTO sample reported in the literature. PVDF–ZTO also exhibited a promising photon-to-current efficiency of approximately 31%. Our study results indicate that PVDF–ZTO can potentially be used in piezophotocatalytic and PEC applications.